John Adams: Gondolatok a kormányzásról - Fenyvesi, Balázs (Kultúratudományi Szemle, 2022)
Thoughts on government John Adams This publication aims to give a complete translation of Thoughts on Government (1776), one of John Adams' main writings, who is a core figure of American conservativism; with a brief introduction and notes by the translator. The text can be considered as Adams' political credo, and is primarily about to argue in favour of the Rule of Law, the separation of powers, and the free and independent judicial power.